Pelayanan Pencatatan Pernikahan Dikantor Urusan Agama Kecamatan Mariso Kota Makassar - Lestari, Nova Ayu; Alyas, Alyas; Parawangi, Anwar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to determine the marriage registration service at the Office of Religious Affairs, Mariso District, Makassar City. This study used descriptive qualitative research, which was a form of research that provided an overview as the kind of data collected techniques used observation, interviews with a number of informants and documentation. The results showed that the service for recording marriage at the Office of Religious Affairs in Mariso District, Makassar City was not fully implemented optimally, seen from the tangibles aspect, it showed that the quality of service was constrained by inadequate facilities and infrastructure so that people were less comfortable waiting for services, realibility aspects in the approach of officers with the community, each individual pleased and satisfied  the community besides that the facilities and infrastructure support satisfyingly, the aspect of fast service response carried out when there were no community constraints with in the predetermined requirements. And the aspect of emphaty used an emotional approach when there were problems of service. Maximizing good service so that people feel satisfied.Keywords : Registration Service, Marriage